Synergistic antibacterial mechanism of the Lactobacillus crispatus surface layer protein and nisin on Staphylococcus saprophyticus - Zhilan Sun (Nature Portfolio, 2017)
Abstract SlpB, a surface layer protein isolated from Lactobacillus crispatus, has the potential to enhance the antimicrobial activity of nisin. Previous research indicated that, when combined with nisin, SlpB acted synergistically to inhibit Staphylococcus saprophyticus growth, thus extending the shelf life of chicken meat. In order to understand how SlpB enhances the antibacterial activity of nisin, electron microscopy, confocal laser scanning microscopy, flow cytometry and transmembrane electrical potential analysis were used to study cell wall organization and cell membrane integrity. No remarkable bacteriolytic effects were observed, indicating that cell death could not be attributed to cell lysis, although SlpB caused dramatic modifications of cell wall, thereby altering cell shape. The combination of SlpB and nisin also induced the release of ATP or UV-absorbing materials, as well as sudden dissipation of the transmembrane electrical potential by compromising membrane integrity. Considering that SlpB led to structural disorganization of the cell wall, and nisin access is enhanced to form a stable pore, cell death is a predictable outcome. SlpB significantly enhanced the effect of nisin at half of the minimum inhibitory concentration, which resulted in cell death by destroying the cell wall and cell membrane, therefore providing a new, feasible approach in food preservation.